Block Chain Technology to Analyse a Cloud Computing Security Framework - Mr.K.Anil, Dr.X.S.Asha Shiny (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The phrase "cloud computing" is in flux right now. It is a business strategy that offers services that are supplied and consumed instantly, anywhere, at any time, over any network that is accessible, utilising computing devices that use cloud computing technologies. Although cloud is advantageous because it offers controlled, tailored, and on-demand resources, it also presents the biggest challenge. The security risk to the cloud system, particularly the user group, must be overcome in computing. These days, cloud security is a significant privacy challenge for both users and cloud service providers. The cloud security framework issues are discussed in this study. Most of the time, new technologies enter our lives in ways we never could have predicted. One such technology is blockchain. . In this article, we offered an architecture and framework for cloud security and its problematic areas. Based on that, we had visualised the main cloud security issue areas and showed how the combination of blockchain and cloud computing had a significant impact on cloud security features.